2019
DOI: 10.3390/molecules24102021
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (3-Benzyl-5-hydroxyphenyl)carbamates as New Antitubercular Agents with Potent In Vitro and In Vivo Efficacy

Abstract: A series of 3-amino-5-benzylphenol derivatives were designed and synthesized. Among them, (3-benzyl-5-hydroxyphenyl)carbamates were found to exert good inhibitory activity against M. tuberculosis H37Ra, H37Rv and clinically isolated multidrug-resistant M. tuberculosis strains (MIC = 0.625–6.25 μg/mL). The privileged compounds 3i and 3l showed moderate cytotoxicity against cell line A549. Compound 3l also exhibited potent in vivo inhibitory activity on a mouse infection model via the oral administration. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Carbamate 115 (Figure ) was published in 2019 as part of a SAR study . This molecule showed an MIC 90 value of 1.8 μM against autoluminescent Mtb H37Ra but had weaker activity against Mtb H37Rv and MDR strains (MICs 11–23 μM) and low cytotoxicity against A549 cells (CC 50 64 μM).…”
Section: Preclinical Promisesmentioning
confidence: 99%
“…Carbamate 115 (Figure ) was published in 2019 as part of a SAR study . This molecule showed an MIC 90 value of 1.8 μM against autoluminescent Mtb H37Ra but had weaker activity against Mtb H37Rv and MDR strains (MICs 11–23 μM) and low cytotoxicity against A549 cells (CC 50 64 μM).…”
Section: Preclinical Promisesmentioning
confidence: 99%
“…The results suggest that the steric effect and lipophilicity of the ester group are crucial for antimicrobial activity. It should be noted that compound 6h also exhibited the most potent antitubercular activity in the previous study …”
Section: Resultsmentioning
confidence: 69%
“…In the study of new antitubercular agents, a series of (3‐benzyl‐5‐hydroxyphenyl)carbamates were designed and synthesized. One privileged compound displayed good in vitro and in vivo inhibitory activity against Mycobacterium tuberculosis . During further research, the compound was also found to exhibit potent inhibitory activity against S. aureus .…”
Section: Introductionmentioning
confidence: 97%
“…Herein, the four individual properties MW, log P , HBD, and HBA as well as PSA and ROTB were analyzed for 39 TB drugs (approved and candidates in clinical trials) and 1271 synthetic anti-tubercular compounds reported in 40 publications between 2006 to early 2020. Instant JChem 17.29.0 [Instant JChem 17.29.0, 2017 ChemAxon Ltd. ()] was used for calculation of physiochemical properties…”
Section: Introductionmentioning
confidence: 99%